PENGERINGAN BIJI PALA (Myristica fragrans Houtt) MENGGUNAKAN ENERGI RADIASI MATAHARI DAN LPG (Liquefied Petroleum Gas) DENGAN BANTUAN ALAT PENGERING - Rizaldi Akbar Kaplale; Handry Rawung; Dedie Tooy (COCOS, 2018)
ABSTRACT Nutmeg seeds are a commodity that are well known in Indonesia, making nutmeg seeds as an important spice since the past. This study aims to analyze several drying parameters in the nutmeg drying process such as temperature, relative humadity, reduction in weight of the material, drying rate, intensity of solar radiation in drying using solar energy and LPG (Liquefied Petroleum Gas). This research was conducted at the Agricultural Engineering Laboratory, Faculty of Agriculture at Sam Ratulangi University. This research uses descriptive method of temperature in the dryer on rack 1 ranges from 35.7°C - 59.2°C, rack 2: 35.6°C - 58.4°C and rack 3: 33.6°C - 46.6°C while the ambient temperature from 30°C - 37°C. The relative humadity of the environment during drying is 60% - 88% and in the dryer is, rack 1: 25% - 66%, rack 2: 23% - 66%, and rack 3: 26%- 74%. During the drying process there is a decrease in water content from 61.52% bk dropped to an averange rack 1: 34.32%, rack 2: 33.34% and rack 3: 36.42%. The highest intensity of solar radiation reaches is 872.25 watts/hour and the lowest is 407.05 watts/hour. Drying using solar energy and LPG will speed up the drying process. Key words: nutmeg, dryer, LPG, solar energy